Biomimetic Growth of Ultrathin Silica Sheets Using Artificial Amphiphilic Peptides. Issue 17 (17th September 2015) - Lutz, Helmut; Jaeger, Vance; Berger, Rüdiger; Bonn, Mischa; Pfaendtner, Jim; Weidner, Tobias
Abstract : Biomimetic silica sheets synthesized by synthetic leucine–lysine peptides with different foldings from tetramethyl orthosilicate are presented. The nanometer‐thin and micrometer‐size silica sheets are stable and self‐supported. Moreover, the morphology of the sheets is controlled by the secondary structure of the peptides when interacting with the silica.